2016
DOI: 10.1038/srep30629
|View full text |Cite
|
Sign up to set email alerts
|

Snoring Sounds Predict Obstruction Sites and Surgical Response in Patients with Obstructive Sleep Apnea Hypopnea Syndrome

Abstract: Snoring sounds generated by different vibrators of the upper airway may be useful indicators of obstruction sites in patients with obstructive sleep apnea hypopnea syndrome (OSAHS). This study aimed to investigate associations between snoring sounds, obstruction sites, and surgical responses (≥50% reduction in the apnea-hypopnea index [AHI] and <10 events/hour) in patients with OSAHS. This prospective cohort study recruited 36 OSAHS patients for 6-hour snoring sound recordings during in-lab full-night polysomn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…4 Obstructions other than surgical sites (adenoid and palatine tonsils), such as tongue base, lingual tonsil and supraglottic obstruction, may cause surgical non-success. 19,20 In our previous study, 7 Therefore, further studies with a larger sample size with the extended age spectrum and drug-induced examinations are warranted to confirm our results and inferences. SSE of high frequency is a potential biomarker for severe OSA, and analysis of this specific SSE may help to predict surgical success and monitor surgical outcomes.…”
Section: Comparisons With Other Studiessupporting
confidence: 67%
See 3 more Smart Citations
“…4 Obstructions other than surgical sites (adenoid and palatine tonsils), such as tongue base, lingual tonsil and supraglottic obstruction, may cause surgical non-success. 19,20 In our previous study, 7 Therefore, further studies with a larger sample size with the extended age spectrum and drug-induced examinations are warranted to confirm our results and inferences. SSE of high frequency is a potential biomarker for severe OSA, and analysis of this specific SSE may help to predict surgical success and monitor surgical outcomes.…”
Section: Comparisons With Other Studiessupporting
confidence: 67%
“…Obstructions other than surgical sites (adenoid and palatine tonsils), such as tongue base, lingual tonsil and supraglottic obstruction, may cause surgical non‐success . In our previous study, a snoring sound of 850‐2000 Hz was related to tongue base obstruction in adulthood OSA, and Xu reported that a snoring sound >800 Hz was related to lower level obstruction in adulthood OSA. Accordingly, there may be a link between high‐frequency snoring sounds and lower level obstructions.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The procedure used for drug-induced sleep in a CT room unit equipped with standard anaesthetic monitoring (oxygen saturation, non-invasive blood pressure, and electrocardiography) was similar to our previous reports 36 37 . Despite drug-induced sleep has been proven its safety in severe OSA patients 38 , we closely monitored the occurrence of mean arterial pressure <65 mmHg, oxygen saturation <90%, and persistent apnea.…”
Section: Methodsmentioning
confidence: 78%